Grasping The Management Of Islamic Education Amidst The Digital Era - Mulyadi Mulyadi (International Journal of Public Health, 2024)
Since technology revolutionized the world, business transformation has been total, especially in developed countries. As a result, the country's leaders adopted an unprecedented policy of implementing technology in all areas. This has resulted in almost all activities in the world using technology to continue operations, even though it is not yet fully ready. Including the application of technology in increasingly digital education, enabling the education industry to be sustainable, more affordable, and achieve optimal goals. Specifically, this research aims to understand how technology is applied in the governance of Islamic education. For this purpose, we used electronic data searches via Google Scholar and other applications. Analysis is carried out using system coding, evaluation and in-depth interpretation of the data to produce valid and reliable findings. This study used a qualitative data review design on publications published between 2010 and 2021 to obtain the most recent data. Based on the discussion of the data findings, it can be concluded that the management of Islamic educational institutions appreciates the use of digital technology or websites in graduate preparation programs that balance world interests and preparation for the hereafter, with a focus on shared knowledge and skills improvement (upskill).